Estimating farmers' willingness to pay for weather index-based crop insurance uptake in West Africa: Insight from a pilot initiative in Southwestern Burkina Faso - William M. Fonta; Safietou Sanfo; Abbi Mamo Kedir; Djiby R. Thiam (Agricultural and Food Economics, 2018)
Weather index-based crop insurance is increasingly becoming important as a risk mitigation strategy that farmers may use to mitigate adverse climate shocks and natural disasters encountered during farming. While Europe, North America, and Asia account for 20.1%, 55%, and 19.5% of the total agricultural insurance premium worldwide, respectively, Africa accounts for only 0.5% of the world insurance industry. One of the key reasons advanced against the low index insurance participation rate in Africa is the failure to involve farm households at the initial conceptualization and design of pilot initiatives. Therefore, the main purpose of this paper is to design an improved participatory methodology that could help elicit information on the value placed by farm households in Southwestern Burkina Faso on a new weather index-based crop insurance management initiative. A key concept in the improved participatory methodology is that of the willingness to pay (WTP) of farm households for the scheme. Knowledge of the maximum amount that farmers are willing to pay for the scheme can help insurance policy providers and public policy makers to design and put in place measures that sustain index insurance schemes in a developing country context and improve welfare among participating farmers.
Keywords: 330; Climate change; Agricultural risk; Adaptation strategy; Weather index-based crop insurance; Contingent valuation method; Willingness to pay; Heckman 2-step estimator